种低能耗恒温泡菜发酵装置 (2017)
本发明公开了种低能耗恒温泡菜发酵装置，其包括墙体(1)、太阳能吸收储能单元、空气源加热储能单元、发酵池管道供热单元以及调温、调湿单元。发酵池管道供热单元通过控制模块控制阀门和水泵切换发酵池管道供热单元的供热模式；调温、调湿单元将中转池(20)热水引入喷淋塔(50)，通过安装在喷淋塔(50)上的抽风扇(51)进行气体循环，实现装置内的升温、增湿。本发明对太阳能和空气热能加以合理利用来实现发酵池的恒温、可控与发酵液动态循环，节能环保的同时，提高了泡菜的加工质量和产量，且使用寿命高，方便人员维护。 The invention discloses a low-energy-consumption and constant-temperature pickle fermentation device. The pickle fermentation device comprises a wall (1), a solar absorbing and energy storing device, an air source heating and energy storing unit, a fermentation vat pipeline heat supply unit and a temperature and humidity adjusting unit. A control module controls a valve and a water pump to switch heat supply modes of the fermentation vat pipeline heat supply unit. The temperature and humidity adjusting unit leads hot water in a transferring tank (20) into a spray tower (50), gas circulation is carried out through an exhaust fan (51) installed on the spray tower (50), and temperature rising and humidity increasing in the device are achieved. The constant-temperature